Forest in the Context of Social Change: Traditional Orientation and Forest Mystification in a Nigerian Forest-Reserve Setting - Fausat Motunrayo Ibrahim (Ural Federal University, 2021)
This article exposits the mystification of forests among people residing in proximity to a forest reserve in southwestern Nigeria. The theory of material engagement and the ecology of human development support the position that the forest is a classical motivator of traditional culture. Still, socio-cultural change is prevalent. As an element of this change, forest-based social cognition warrants systematic examination in the interest of environmental sustainability. This is because the concurrent conveyance of sustainability-promoting immaterial culture across generations is a component of the pathway to a sustainable future. Moreover, systems theory posits that social events affect each other. Since social change is not solitary but encompassing, forest mystification was examined along with other indicators of traditional orientation including attitude towards―religion, ageing, gender; and cultural enthusiasm. The results indicate that forest mystification is still huge and connected with orientations towards ageing and cultural enthusiasm. This exemplifies the Yorùbá social context’s manifestation of continuity as opposed to change in forest culture; and stands in solidarity with traditional African mentality.